2015
DOI: 10.1371/journal.pone.0115855
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 21 Is a Homeostatic Regulator of Macrophage Polarization and Prevents Prostaglandin E2-Mediated M2 Generation

Abstract: Macrophages dictate both initiation and resolution of inflammation. During acute inflammation classically activated macrophages (M1) predominate, and during the resolution phase alternative macrophages (M2) are dominant. The molecular mechanisms involved in macrophage polarization are understudied. MicroRNAs are differentially expressed in M1 and M2 macrophages that influence macrophage polarization. We identified a role of miR-21 in macrophage polarization, and found that cross-talk between miR-21 and the lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 58 publications
5
113
1
1
Order By: Relevance
“…In contrast to the findings by Caescu et al (42), Wang et al (43) reported that miR-21 promoted M1 polarization in peritoneal macrophages and inhibited M2 polarization. In miR-21-KO macrophages, expression levels of M1 markers ( Tnfa, Il12p40, Il1b, and Il6 ) were lower while M2 markers ( Il10, Arg1, Retnla, and Chi3l3 ) were increased remarkably compared to levels in wild type (WT) macrophages (43).…”
Section: Functional Role Of Micrornas In the Regulation Of Macrophcontrasting
confidence: 71%
See 2 more Smart Citations
“…In contrast to the findings by Caescu et al (42), Wang et al (43) reported that miR-21 promoted M1 polarization in peritoneal macrophages and inhibited M2 polarization. In miR-21-KO macrophages, expression levels of M1 markers ( Tnfa, Il12p40, Il1b, and Il6 ) were lower while M2 markers ( Il10, Arg1, Retnla, and Chi3l3 ) were increased remarkably compared to levels in wild type (WT) macrophages (43).…”
Section: Functional Role Of Micrornas In the Regulation Of Macrophcontrasting
confidence: 71%
“…In miR-21-KO macrophages, expression levels of M1 markers ( Tnfa, Il12p40, Il1b, and Il6 ) were lower while M2 markers ( Il10, Arg1, Retnla, and Chi3l3 ) were increased remarkably compared to levels in wild type (WT) macrophages (43). Treatment of WT macrophages with prostaglandin E2 (PGE2), an endogenous lipid mediator produced in inflammation and infection, inhibited miR-21 expression (43). Further studies demonstrated that PGE2 decreased the expression of M1 markers and enhanced the expression of M2 markers (43).…”
Section: Functional Role Of Micrornas In the Regulation Of Macrophmentioning
confidence: 97%
See 1 more Smart Citation
“…Atherosclerosis progression is associated with the predominance of an M1 macrophage phenotype in the plaque, whereas plaques undergoing regression are enriched in M2 macrophages 92 . A growing list of miRNAs is implicated in regulating the balance between the M1 and M2 phenotypes, including miR-let7a 98 , miR-19a 99 , miR-21 100 , miR-27a 101 , miR-33 42 , miR-124 102 , miR-125a 103 , miR-146a 104 , miR-155 105 , miR-214 106 , miR-223 107 . However, few of these have been investigated in the context of atherosclerosis.…”
Section: Mirnas Regulating Leukocyte Recruitment and Activation In Atmentioning
confidence: 99%
“…Macrophages from Socs1 Δmyel mice were induced by injection with 2 ml 3% thioglycollate, and these were harvested 4 days after injection, as previously described (84). Macrophages were stimulated with 100 ng/ml LPS (Sigma-Aldrich), and 24 hours after stimulation, these were harvested for analysis by ChIP assay.…”
Section: Equationmentioning
confidence: 99%